(untitled) (ALKIMIA : Jurnal Ilmu Kimia dan Terapan, 2023)
The rapid development of industry increases lead heavy metal pollution (Pb). The heavy metal lead is known for its toxicity to humans. Adsorption is one way to minimize the negative impact of lead. Increasing the ability of adsorbents through the activation process is very important in the role of minimizing the adverse effects of lead. This study aimed to determine the activity of NaOH-activated Calcium Oxide (CaO) as an adsorbent for lead metal (Pb) ions. FT-IR spectra show Ca-O bond vibrations at wave numbers 842 cm-1 in CaO adsorbent, and 845 cm-1, 781 cm-1 in activated CaO adsorbent. Meanwhile, from the results of the AAS analysis, the adsorption capacity of activated CaO is 3% higher than CaO for the adsorption of lead metal ions.